The contribution of ZIMCHE towards ensuring quality education at tertiary level in Zimbabwe: the case of Zimbabwe Ezekiel Guti University - Muzungu, Shorai Christopher (Midlands State University, 2020)
Today Zimbabwe is awash with graduates from different degree programmes. Each and every year, the country is churning out thousands of graduates from its various universities. It is ranked among one of the most literate countries not only in Southern Africa but the continent at large. Despite such a milestone achievement, the graduates have been facing challenges in getting employment. The major question that might be posed by the writer is, “are these degree programmes relevant and of the quality required by this present global economy? Universities are now focusing on quantity rather than quality of students. That is affecting the quality of graduates that are produced. It is within this streamline that we shall make a close examination of the role that ZIMCHE is playing in contributing towards quality education in the country. The major problem may be lying in the quality of graduates that are being produced in Zimbabwe. The study is focusing on Zimbabwe Ezekiel Guti University in Bindura. The writer used qualitative research study in carrying out this study. KEY